Possible association between vitamin D deficiency and restless legs syndrome - Oran, Mustafa (Dove Medical Press, 2014)
BACKGROUND AND AIM: Restless legs syndrome (RLS) is a distressing sleep disorder that occurs worldwide. Although there have been recent developments in understanding the pathophysiology of RLS, the exact mechanism of the disease has not been well elucidated. An increased prevalence of neurologic and psychiatric diseases involving dopaminergic dysfunction in vitamin D–deficient patients led us to hypothesize that vitamin D deficiency might result in dopaminergic dysfunction and consequently, the development of RLS (in which dopaminergic dysfunction plays a pivotal role). Thus, the aim of this study was to evaluate the relationship between vitamin D deficiency and RLS. METHODS: One hundred and fifty-five consecutive patients, 18–65 years of age, who were admitted to the Department of Internal Medicine with musculoskeletal symptoms and who subsequently underwent neurological and electromyography (EMG) examination by the same senior neurologist, were included in this study. The patients were divided into two groups according to serum 25-hydroxyvitamin D (25(OH)D) (a vitamin D metabolite used as a measure of vitamin D status) level: 36 patients with serum 25(OH)D levels ≥20 ng/mL comprised the normal vitamin D group, and 119 patients with serum 25(OH)D levels <20 ng/mL comprised the vitamin D deficiency group. The two groups were compared for the presence of RLS and associated factors. RESULTS: The two groups were similar in terms of mean age, sex, mean body mass index (BMI), and serum levels of calcium, phosphate, alkaline phosphatase (ALP), and ferritin. The presence of RLS was significantly higher in the vitamin D deficiency group (χ(2)=12.87, P<0.001). Regression analysis showed vitamin D deficiency and serum 25(OH)D level to be significantly associated with the presence of RLS (odds ratio [OR] 5.085, P<0.001 and OR 1.047, P=0.006, respectively). CONCLUSION: The present study demonstrated a possible association between vitamin D deficiency and RLS. Given the dopaminergic effects of vitamin D, 25(OH)D depletion may lead to dopaminergic dysfunction and may have a place in the etiology of RLS. Prospective vitamin D treatment studies are needed to confirm this relationship and to evaluate the efficacy of vitamin D as a treatment for RLS patients.